HISTORY OF PESTICIDE APPLICATION AGAINST LEPTINOTARSA DECEMLINEATA SAY IN UKRAINE - Бондарева, Леся; Мищук, Валерий; Максимчук, Алексей (SWorldJournal, 2021)
The review considers the formation of resistant populations of the most dangerous potato pest of the Colorado potato beetle Leptinotarsa decemlineata Say. on the territory of Ukraine to insecticides of various chemical structure, starting from organochlor